A method for accurately characterizing the degradation degree of SBS polymer in the aging process of SBS / sulfur modified asphalt

CN117990567BActive Publication Date: 2026-10-30HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410126560.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-10-30
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

[0004]本发明是要解决目前硫化反应会干扰对SBS/硫磺改性沥青老化过程中SBS聚合物实际降解程度的判断的技术问题,而提供一种精确表征SBS/硫磺改性沥青老化过程中SBS聚合物降解程度的方法

Benefits of technology

[0033]本发明通过引入硫化补偿因子,对现有的荧光图像中的SBS聚合物相的尺寸变化规律进行修正,反映老化过程中的SBS聚合物降解程度,且具有快速、直观和便捷的优势,解决了用相尺寸表征SBS聚合物降解程度与老化过程中黏弹性能变化规律不相符的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117990567B_ABST
    Figure CN117990567B_ABST
Patent Text Reader

Abstract

The application relates to a method for accurately characterizing the degradation degree of SBS polymer in the aging process of SBS / sulfur modified asphalt, and relates to a method for characterizing the degradation degree of SBS polymer in the aging process of modified asphalt.The application aims to solve the technical problem that the current vulcanization reaction interferes with the judgment of the actual degradation degree of SBS polymer in the aging process of SBS / sulfur modified asphalt.The application firstly performs short-term aging and long-term aging on SBS modified asphalt and SBS / sulfur modified asphalt respectively; then performs fluorescence microscope testing on the two kinds of asphalt in different aging stages respectively, obtains the phase size related quantitative parameters of the two kinds of asphalt under different aging states in the fluorescence testing, calculates a vulcanization compensation factor through Fourier transform infrared spectrum testing, corrects the phase size in the aging process of SBS / sulfur modified asphalt through the vulcanization compensation factor, and uses the corrected phase size to characterize the polymer degradation degree in the aging process of SBS / sulfur modified asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for characterizing the degree of SBS polymer degradation during the aging process of modified asphalt. Background Technology

[0002] SBS-modified asphalt has become a widely used asphalt material in road engineering due to its comprehensive improvement of the low-temperature performance, high-temperature performance, water stability, and fatigue performance of base asphalt. However, due to differences in density, molecular weight, and polarity between SBS modifiers and base asphalt, SBS-modified asphalt is prone to segregation during storage and transportation, thus affecting its actual pavement performance. In engineering practice, sulfur-based stabilizers are typically added for chemical cross-linking. The sulfur reacts with both ends of the asphalt phase and the SBS polymer phase to form chemical cross-links, thereby improving the compatibility of SBS-modified asphalt. On one hand, the sulfur stabilizer undergoes an addition reaction with the unsaturated carbon-carbon double bonds in the polystyrene segments of the SBS copolymer; on the other hand, asphaltenes and polycyclic aromatic compounds can react with the stabilizer at 140℃ to form CS bonds. The addition of sulfur stabilizers makes the aging mechanism of SBS modified asphalt more complex. After aging, the SBS polymer will undergo severe degradation, and the asphalt components and polymer network structure will also change during the aging process. The degree of degradation of SBS polymer directly affects the residual modification effect in the SBS modified asphalt after aging, and thus affects whether the SBS modified asphalt after aging can be regarded as modified asphalt or base asphalt. Therefore, it is necessary to quantitatively characterize the degree of degradation of SBS polymer during the aging process.

[0003] Previous studies have quantified the degree of SBS polymer degradation during aging by analyzing molecular weight, chemical structure, and polymer phase size. Phase size analysis, in particular, is widely used due to its intuitive observation via optical / electron microscopy and ease of operation. However, quantifying the degree of SBS polymer degradation during aging is more challenging for SBS / sulfur-modified asphalt. Besides the reduction in phase size caused by SBS polymer degradation during aging, the presence of sulfur stabilizers and the resulting vulcanization reaction also lead to SBS polymer refinement. This can interfere with the assessment of the actual degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt, and even lead to contradictory results. Therefore, it is necessary to distinguish between the different changes in SBS polymer caused by vulcanization and aging reactions in SBS / sulfur-modified asphalt, and to develop a precise method for characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt. This is of great significance. Summary of the Invention

[0004] The present invention aims to solve the technical problem that the current vulcanization reaction interferes with the judgment of the actual degree of degradation of SBS polymer during the aging process of SBS / sulfur modified asphalt, and provides a method for accurately characterizing the degree of degradation of SBS polymer during the aging process of SBS / sulfur modified asphalt.

[0005] The method of the present invention for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt is carried out according to the following steps:

[0006] I. Preparation of SBS modified asphalt and SBS / sulfur modified asphalt: The two types of asphalt were subjected to short-term aging tests and long-term aging tests, respectively.

[0007] 2. The morphological characteristics of the two types of asphalt were analyzed, and fluorescence images of the two types of asphalt under three aging states: no aging, short-term aging, and long-term aging were obtained. The Image-pro-plus software was used to perform quantitative analysis on the fluorescence images under the six aging states, calculate the number of SBS polymer phase particles and the particle size of a single particle in each fluorescence image, and draw the SBS polymer particle size distribution map based on the calculated data.

[0008] III. Combining the SBS polymer particle size distribution map and fluorescence image, we define three quantitative parameters: phase size, phase dispersion, and two phases.

[0009] Phase size represents the average particle size of the SBS polymer phase;

[0010] Phase dispersion indicates the uniformity between different particle sizes within an SBS polymer;

[0011] The phase ratio represents the proportion of the bitumen phase to the SBS polymer phase;

[0012] The formulas for the three quantization parameters are shown below:

[0013]

[0014]

[0015]

[0016] In the formula: n is the number of SBS polymer particles in the fluorescence image;

[0017] Polymer area It represents the area of ​​the SBS polymer phase within the fluorescence image;

[0018] Asphalt area The area of ​​the bituminous phase within the fluorescence image;

[0019] i is the sequence number of the SBS polymer particles in the fluorescence image, ranging from 0 to n. The sorting order is based on the area of ​​the SBS polymer particles in the fluorescence image from smallest to largest.

[0020] IV. Calculation of Sulfation Compensation Factor The specific steps are as follows:

[0021] 1. Infrared spectral analysis was performed on SBS modified asphalt and SBS / sulfur modified asphalt under three conditions: no aging, short-term aging, and long-term aging. The wavenumber range for the test was 4000 cm⁻¹. -1 ~400cm -1 The resolution is 0.4cm. -1 The corresponding infrared spectra were obtained respectively;

[0022] 2. For infrared spectra with a wavenumber of 699 cm⁻¹ -1 and 966cm -1 Quantitative analysis was performed on two characteristic groups, with a wavenumber of 699 cm⁻¹. -1 The vibration at this point represents the bending vibration of the CH bond in the benzene ring of polystyrene, with a wavenumber of 966 cm⁻¹. -1 The vibration at 699 cm⁻¹ represents the trans-vibration of the C=C bond in polybutadiene. The quantitative analysis method is based on Lambert-Beer's law, employing the baseline method and utilizing the analysis function of Omnic software to calculate the vibration at 699 cm⁻¹. -1 and 966cm -1 Characteristic peak area;

[0023] ① Based on the characteristic group analysis method, calculate the peak areas of the two specific functional groups, which are 699 cm⁻¹ respectively. -1 polystyrene groups and 966cm -1 The polybutadiene group is selected with a wavenumber range of 1800 cm⁻¹. -1 Up to 650cm -1 The peak area is used as a reference peak area to eliminate the influence of film thickness; the relative peak areas are obtained by calculating the two characteristic peak areas and the reference peak area, which are denoted as styrene index (SI) and butadiene index (BI), respectively, and the calculation formula is shown below;

[0024]

[0025]

[0026] ② Based on Formulas 4 and 5 above, calculate the styrene index and butadiene index of the two types of asphalt in the infrared spectra under the three aging states, and calculate the difference between the styrene index and the butadiene index in the vulcanization reaction and the aging reaction.

[0027] ③ Sulfurization compensation factor The sulfidation compensation factors of the two modified asphalts under short-term and long-term aging were calculated using the following formula.

[0028]

[0029] In the formula: △SI and △BI are the differences in styrene index and butadiene index, respectively, and their absolute values ​​are taken. It is a sulfurization compensation factor;

[0030] ④ Take the minimum value of the sulfurization compensation factor in SBS modified asphalt under the two aging conditions as the compensation benchmark; standardize the sulfurization compensation factors of SBS / sulfur modified asphalt under short-term and long-term aging. The standardized sulfurization compensation factor is the corresponding compensation factor divided by the compensation benchmark; then multiply the phase size before compensation by the corresponding standardized sulfurization compensation factor to obtain the phase size after compensation. The smaller the phase size after compensation, the more severe the degradation and the worse the asphalt performance.

[0031] This invention first subjects SBS-modified asphalt and SBS / sulfur-modified asphalt to short-term and long-term aging, respectively. Then, fluorescence microscopy tests are performed on the two types of asphalt at different aging stages to obtain quantitative parameters related to phase size under different aging states of the two types of asphalt under fluorescence testing. The sulfurization compensation factor is calculated by Fourier transform infrared spectroscopy. The phase size of SBS / sulfur-modified asphalt during aging is corrected by the sulfurization compensation factor. The corrected phase size is used to characterize the degree of polymer degradation during the aging process of SBS / sulfur-modified asphalt.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] This invention introduces a sulfurization compensation factor to correct the size change pattern of the SBS polymer phase in existing fluorescence images, reflecting the degree of SBS polymer degradation during the aging process. It has the advantages of being fast, intuitive, and convenient, and solves the problem that the use of phase size to characterize the degree of SBS polymer degradation does not match the change pattern of viscoelastic properties during the aging process. Attached Figure Description

[0034] Figure 1 This is a schematic diagram illustrating the preparation process of two modified asphalts;

[0035] Figure 2 The fluorescence image shows the SBS-modified asphalt before aging.

[0036] Figure 3 Fluorescence image of SBS / sulfur-modified asphalt before aging;

[0037] Figure 4 Fluorescence image of SBS modified bitumen after short-term aging;

[0038] Figure 5 Fluorescence image of SBS / sulfur-modified asphalt after short-term aging;

[0039] Figure 6 Fluorescence image of SBS modified asphalt after long-term aging;

[0040] Figure 7 Fluorescence image of SBS / sulfur-modified asphalt after long-term aging;

[0041] Figure 8 The particle size distribution of SBS-modified asphalt polymer before aging is shown.

[0042] Figure 9 The particle size distribution of SBS / sulfur-modified bitumen polymer before aging is shown.

[0043] Figure 10 The particle size distribution of SBS-modified asphalt polymer after short-term aging is shown in the diagram.

[0044] Figure 11 The particle size distribution of SBS / sulfur-modified asphalt polymer after short-term aging is shown.

[0045] Figure 12 This is a particle size distribution diagram of SBS-modified asphalt polymer after long-term aging.

[0046] Figure 13 The particle size distribution of SBS / sulfur-modified asphalt polymer after long-term aging is shown in the figure.

[0047] Figure 14 This is a schematic diagram for quantitative analysis of characteristic functional groups;

[0048] Figure 15 The infrared spectra of the two types of asphalt in their unaged state are shown.

[0049] Figure 16 The infrared spectrum of SBS modified asphalt after aging;

[0050] Figure 17 Infrared spectrum of SBS / sulfur-modified asphalt after aging;

[0051] Figure 18 This is a graph showing the difference between the styrene index and the butadiene index during the vulcanization and aging reactions. Detailed Implementation

[0052] Specific Implementation Method 1: This implementation method is a method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt, specifically carried out according to the following steps:

[0053] I. Preparation of SBS modified asphalt and SBS / sulfur modified asphalt: The two types of asphalt were subjected to short-term aging tests and long-term aging tests, respectively.

[0054] 2. The morphological characteristics of the two types of asphalt were analyzed, and fluorescence images of the two types of asphalt under three aging states: no aging, short-term aging, and long-term aging were obtained. The Image-pro-plus software was used to perform quantitative analysis on the fluorescence images under the six aging states, calculate the number of SBS polymer phase particles and the particle size of a single particle in each fluorescence image, and draw the SBS polymer particle size distribution map based on the calculated data.

[0055] III. Combining the SBS polymer particle size distribution map and fluorescence image, we define three quantitative parameters: phase size, phase dispersion, and two phases.

[0056] Phase size represents the average particle size of the SBS polymer phase;

[0057] Phase dispersion indicates the uniformity between different particle sizes within an SBS polymer;

[0058] The phase ratio represents the proportion of the bitumen phase to the SBS polymer phase;

[0059] The formulas for the three quantization parameters are shown below:

[0060]

[0061]

[0062]

[0063] In the formula: n is the number of SBS polymer particles in the fluorescence image;

[0064] Polymer area It represents the area of ​​the SBS polymer phase within the fluorescence image;

[0065] Asphalt area The area of ​​the bituminous phase within the fluorescence image;

[0066] i is the sequence number of the SBS polymer particles in the fluorescence image, ranging from 0 to n. The sorting order is based on the area of ​​the SBS polymer particles in the fluorescence image from smallest to largest.

[0067] IV. Calculation of Sulfation Compensation Factor The specific steps are as follows:

[0068] 1. Infrared spectral analysis was performed on SBS modified asphalt and SBS / sulfur modified asphalt under three conditions: no aging, short-term aging, and long-term aging. The wavenumber range for the test was 4000 cm⁻¹. -1 ~400cm-1 The resolution is 0.4cm. -1 The corresponding infrared spectra were obtained respectively;

[0069] 2. For infrared spectra with a wavenumber of 699 cm⁻¹ -1 and 966cm -1 Quantitative analysis was performed on two characteristic groups, and the 699 cm⁻¹ was calculated. -1 and 966cm -1 Characteristic peak area, with wavenumber 699cm² -1 The vibration at this point represents the bending vibration of the CH bond in the benzene ring of polystyrene, with a wavenumber of 966 cm⁻¹. -1 The vibration at this point represents the reverse vibration of the C=C bond in polybutadiene;

[0070] ① Based on the characteristic group analysis method, calculate the peak areas of the two specific functional groups, which are 699 cm⁻¹ respectively. -1 polystyrene groups and 966cm -1 The polybutadiene group is selected with a wavenumber range of 1800 cm⁻¹. -1 Up to 650cm -1 The peak area is used as a reference peak area to eliminate the influence of film thickness; the relative peak areas are obtained by calculating the two characteristic peak areas and the reference peak area, which are denoted as styrene index (SI) and butadiene index (BI), respectively, and the calculation formula is shown below;

[0071]

[0072]

[0073] ② Based on Formulas 4 and 5 above, calculate the styrene index and butadiene index of the two types of asphalt in the infrared spectra under the three aging states, and calculate the absolute values ​​of the difference between the styrene index and the butadiene index in the vulcanization reaction and the aging reaction.

[0074] ③ Sulfurization compensation factor The sulfidation compensation factors of the two modified asphalts under short-term and long-term aging were calculated using the following formula.

[0075]

[0076] In the formula: △SI and △BI are the differences in styrene index and butadiene index, respectively, and their absolute values ​​are taken. It is a sulfurization compensation factor;

[0077] ④ Take the minimum value of the sulfurization compensation factor in the SBS modified asphalt under the two aging states as the compensation benchmark; standardize the sulfurization compensation factors of the SBS / sulfur modified asphalt under short-term and long-term aging. The standardized sulfurization compensation factor is the corresponding compensation factor divided by the compensation benchmark; then multiply the phase size before compensation by the corresponding standardized sulfurization compensation factor to obtain the phase size after compensation. The phase size after compensation is used to intuitively judge the degree of degradation of SBS polymer in aged SBS / sulfur modified asphalt.

[0078] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the preparation method of SBS modified asphalt in step one is as follows:

[0079] 1. Shear 90# base asphalt and linear SBS1301 at 180℃ and 4000rpm for 0.5h; the mass of the linear SBS1301 is 5% of the mass of 90# base asphalt.

[0080] 2. The sheared sample is then placed in a mechanical mixer and stirred at 500 rpm for 2 hours to obtain SBS modified asphalt. Everything else is the same as in Specific Implementation Method 1.

[0081] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One in that the preparation method of SBS / sulfur modified asphalt described in step one is as follows:

[0082] 1. Shear 90# base asphalt and linear SBS1301 at 180℃ and 4000rpm for 0.5h; the mass of the linear SBS1301 is 5% of the mass of 90# base asphalt.

[0083] 2. The sheared sample is first placed in a mechanical stirrer and stirred at 500 rpm for 1 hour. Then, sulfur stabilizer is added and stirring is continued for 1.5 hours, allowing the stabilizer to react with the 90# base asphalt and the SBS polymer phase, resulting in chemical cross-linking and obtaining SBS / sulfur modified asphalt. The mass of the sulfur stabilizer is 0.15% of the mass of the 90# base asphalt. Other steps are the same as in Specific Embodiment 1.

[0084] Specific Implementation Method Four: This implementation method differs from Specific Implementation Method Three in that the short-term aging described in step one is carried out in a film drying oven (TFOT) under aging conditions of 163°C for 5 hours. Everything else is the same as in Specific Implementation Method Three.

[0085] Specific Implementation Method Five: This implementation method differs from Specific Implementation Method Four in that: the sample after short-term aging in step one is placed in a pressure aging vessel (PAV) for long-term aging. The pressure aging conditions are: 2.1 MPa ± 0.1 Ma pressure, aging at 100°C for 20 hours to obtain the sample after long-term aging. Everything else is the same as in Specific Implementation Method Four.

[0086] Specific Implementation Method Six: This implementation method differs from Specific Implementation Method Five in that the fluorescence image in step two is obtained using a CSM-900E series fluorescence microscope at 400x magnification. Everything else is the same as in Specific Implementation Method Five.

[0087] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Method Six in that step four uses a Bruker VERTEX 70 series Fourier transform infrared spectrometer to analyze the infrared spectrum. Everything else is the same as in Specific Implementation Method Six.

[0088] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Method Seven in that the quantitative analysis method described in step four, section two is based on the Lambert-Beer law, employs the baseline method, and utilizes the analysis function of the Omnic software to calculate 699cm. -1 and 966cm -1 The peak area of ​​the characteristic peak. Everything else is the same as in Specific Implementation Method Seven.

[0089] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Method Eight in that: in step four ②, the styrene index difference in the aging reaction is the unaged styrene index minus the aged styrene index; in step four ②, the butadiene index difference in the aging reaction is the unaged butadiene index minus the aged butadiene index. Everything else is the same as in Specific Implementation Method Eight.

[0090] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Method Nine in that: in step four, the compensated phase size is used to visually determine the degree of degradation of the SBS polymer in the aged SBS / sulfur-modified asphalt. The smaller the compensated phase size, the more severe the degradation and the worse the asphalt performance. Everything else is the same as in Specific Implementation Method Nine.

[0091] The invention was verified using the following experiments:

[0092] Experiment 1: This experiment is a method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt. It was conducted according to the following steps:

[0093] In this experiment, two types of asphalt were used: SBS-modified asphalt and SBS / sulfur-modified asphalt. SBS-modified asphalt was prepared using 90# base asphalt and linear SBS1301; SBS / sulfur-modified asphalt was prepared using 90# base asphalt, linear SBS1301, and a sulfur stabilizer. The stabilizer was commercially available elemental sulfur, a yellow powder at room temperature, frequently used as a stabilizer for asphalt-based materials. Both types of asphalt were subjected to short-term and long-term aging tests to prepare pre- and post-aging samples for subsequent testing.

[0094] The specific preparation process includes the following steps:

[0095] 1. In order to produce SBS modified asphalt and SBS / sulfur modified asphalt, 90# base asphalt and 5% by mass of linear SBS1301 were sheared at 180℃ and 4000rpm for 0.5h.

[0096] 2. The sheared samples were divided into two groups, namely the first group and the second group. The first group was put into a mechanical mixer and stirred at 500 rpm for 2 hours to obtain SBS modified asphalt (without stabilizer).

[0097] 3. The second group is first put into a mechanical mixer and stirred at 500 rpm for 1 hour. Then, 0.15% sulfur stabilizer by mass is added and stirring is continued for 1.5 hours. This allows the stabilizer to react with the asphalt phase (90# base asphalt) and the polymer (SBS) phase to produce chemical cross-linking, thus obtaining SBS / sulfur modified asphalt.

[0098] Samples of two types of asphalt were obtained under unaged, short-term aged, and long-term aged conditions: SBS modified asphalt and SBS / sulfur modified asphalt were subjected to short-term and long-term aging, respectively. The short-term aging was carried out in a thin-film oven (TFOT) at 163℃ for 5 hours. The samples after short-term aging were placed in a pressure aging vessel (PAV) for long-term aging at 2.1MPa±0.1Ma at 100℃ for 20 hours to obtain the samples after long-term aging.

[0099] Fluorescence microscopy testing specifically includes the following steps:

[0100] 1. The morphological characteristics of the two types of asphalt were analyzed. A CSM-900E series fluorescence microscope was used to observe the fluorescence images of the two types of asphalt under three aging states: no aging, short-term aging, and long-term aging. Figures 2-7 Fluorescence images of two types of asphalt under different aging conditions are shown.

[0101] 2. Image-pro-plus software was used to perform quantitative analysis on the fluorescence images under each aging state. The number of SBS polymer phase particles and the particle size of individual particles were calculated for each fluorescence image. Based on the calculated data, an SBS polymer particle size distribution map was plotted. Figures 8-13 The particle size distribution of SBS polymers in two types of asphalt under different aging conditions is shown.

[0102] 3. Based on the particle size distribution diagram of SBS polymer, three quantitative parameters were defined: phase size, phase dispersion, and two phases.

[0103] Phase size represents the average particle size of the SBS polymer phase;

[0104] Phase dispersion indicates the uniformity between different particle sizes within an SBS polymer;

[0105] The phase ratio represents the proportion of the bitumen phase to the SBS polymer phase;

[0106] The expressions for the three quantization parameters are as follows:

[0107]

[0108]

[0109]

[0110] In the formula: n is the number of SBS polymer particles in the fluorescence image;

[0111] Polymer area It represents the area of ​​the SBS polymer phase within the fluorescence image;

[0112] Asphalt area The area of ​​the bituminous phase within the fluorescence image;

[0113] i is the sequence number of the SBS polymer particles in the fluorescence image, ranging from 0 to n. The sorting order is based on the area of ​​the SBS polymer particles in the fluorescence image from smallest to largest.

[0114] The calculated data is shown in Table 1.

[0115] Table 1. Quantitative analysis data of SBS polymer phase during aging process.

[0116]

[0117] Table 1 shows that, regarding the effect of the vulcanization reaction on the particle size of SBS polymer, after adding the stabilizer, the phase size of the SBS / sulfur-modified asphalt in the unaged state significantly decreased, as did the phase dispersion, while the two phases increased. This indicates that the particle size distribution of the SBS polymer becomes narrower and more uniform after the addition of sulfur. During the aging process, the phase size of the SBS polymer in both types of modified asphalt also decreased significantly after aging, accompanied by a decrease in the two phases. The vulcanization reaction leads to a decrease in the phase size of the SBS polymer and an increase in the number of particles; while the aging reaction leads to a decrease in both particle size and number due to polymer degradation. Therefore, particle size alone cannot determine the true degree of degradation of the SBS polymer in SBS / sulfur-modified asphalt. Table 1 shows that the SBS polymer phase sizes before and after the vulcanization reaction are 5.91 μm and 4.25 μm, respectively. After long-term aging, the SBS polymer phase sizes of the two types of asphalt are 3.38 μm and 2.82 μm, respectively. It can be seen that the SBS / sulfur modified asphalt does have a smaller phase size after long-term aging. However, the rheological properties of the SBS / sulfur modified asphalt are better than those of the SBS modified asphalt after long-term aging (common knowledge). This means that although phase size is an intuitive and clearly physical characterization parameter, using it directly will lead to contradictory results.

[0118] The steps for calculating the sulfidation compensation factor are as follows:

[0119] 1. The infrared spectrum was analyzed using a Bruker VERTEX 70 series Fourier transform infrared spectrometer (FTIR). The wavenumber range was 4000 cm⁻¹. -1 ~400cm -1 The resolution is 0.4cm. -1 The infrared spectra of SBS modified asphalt and SBS / sulfur modified asphalt were obtained under three conditions: no aging, short-term aging, and long-term aging. Figures 15-17 As shown;

[0120] 2. For infrared spectra with a wavenumber of 699 cm⁻¹ -1 and 966cm -1 Quantitative analysis was performed on two characteristic groups, with a wavenumber of 699 cm⁻¹. -1 The point is the bending vibration of the CH bond in the benzene ring of polystyrene, 966 cm⁻¹. -1 This represents the trans vibration of the C=C bond in polybutadiene; the quantitative analysis method is based on the Lambert-Beer law, employing the baseline method and utilizing the analysis function of Omnic software to calculate the 699 cm⁻¹ vibration. -1 and 966cm -1 The peak area of ​​the characteristic peak is calculated as follows: Figure 14 As shown;

[0121] ① Based on the characteristic group analysis method, calculate the peak areas of the two specific functional groups, which are 699 cm⁻¹ respectively.-1 polystyrene groups and 966cm -1 The polybutadiene group is selected with a wavenumber range of 1800 cm⁻¹. -1 Up to 650cm -1 The peak area is used as a reference peak area to eliminate the influence of film thickness; the relative peak areas are obtained by calculating the two characteristic peak areas and the reference peak area, which are denoted as styrene index (SI) and butadiene index (BI), respectively, and the calculation formula is shown below;

[0122]

[0123]

[0124] ② Calculate according to Formulas 4 and 5 above. Figures 15 to 17 The styrene index and butadiene index of two types of asphalt under three aging conditions were studied, and the absolute values ​​of the difference between the styrene index and the butadiene index in the vulcanization reaction and the aging reaction were calculated. The results are shown in Table 2.

[0125] Table 2 Infrared spectral parameters during the aging process of two types of asphalt

[0126]

[0127] Figure 18 A graph showing the difference between the styrene index and butadiene index during vulcanization and aging reactions, from... Figure 18 As can be seen, the styrene index (SI) and butadiene index (BI) show different differences during the vulcanization and aging reactions. During the vulcanization reaction, the difference in styrene index is only 0.0005, while the difference in butadiene index is 0.0031. This indicates that during the vulcanization reaction, mainly the butadiene index decreases, and the styrene index participates very little in the reaction. However, both the styrene and butadiene indices show more significant changes during short-term and long-term aging. Therefore, the differences in styrene and butadiene indices during vulcanization and aging reactions can be used to calculate the vulcanization compensation factor and correct the phase size in fluorescence microscopy tests.

[0128] ③ By correcting the phase size of SBS / sulfur modified asphalt, the influence of sulfidation reaction on phase size during aging is separated. The phase size of SBS / sulfur modified asphalt in Table 1 is compensated and corrected by calculating the sulfidation compensation factor. The sulfidation compensation factor can be calculated by the following formula, and the calculation results are shown in Table 3.

[0129]

[0130] In the formula: △SI and △BI are the differences in styrene index and butadiene index, respectively, and their absolute values ​​are taken. It is a sulfurization compensation factor; This is the standardized vulcanization compensation factor;

[0131] The sulfidation compensation factor is calculated according to Formula 6. The compensation factors for short-term aging and long-term aging of the two types of asphalt are as follows:

[0132] The compensation factors for short-term and long-term aging of SBS modified asphalt are 0.461 (0.0041 divided by 0.0089, data in Table 2) and 0.456 (0.0057 divided by 0.0125, data in Table 2), respectively.

[0133] The compensation factors for short-term and long-term aging of SBS / sulfur modified asphalt are 0.618 (0.0042 divided by 0.0068, data in Table 2) and 0.580 (0.0094 divided by 0.0162, data in Table 2);

[0134] Since SBS modified asphalt does not contain sulfur stabilizers, no correction is needed; therefore, the vulcanization compensation factor is 1. The minimum compensation factor for SBS modified asphalt under the two aging conditions is 0.456, corresponding to long-term aging. Therefore, the compensation factor for long-term aging vulcanization of SBS modified asphalt is used as the compensation benchmark. The vulcanization compensation factors for short-term and long-term aging of SBS / sulfur modified asphalt are standardized. The standardized vulcanization compensation factors are the corresponding compensation factors divided by the compensation benchmark, which are 1.35 (0.618 divided by 0.456) and 1.27 (0.580 divided by 0.456), respectively. Multiplying the pre-compensation phase size by the corresponding standardized vulcanization compensation factor yields the post-compensation phase size. The smaller the post-compensation phase size, the more severe the degradation and the worse the asphalt performance.

[0135] Table 3 Phase sizes during the aging process of the two types of asphalt before and after correction.

[0136]

[0137] As shown in Table 3, the phase size of the modified SBS / sulfur-modified asphalt increased significantly in both short-term and long-term aging conditions, indicating that the phase size change during aging eliminated the influence of the sulfurization reaction. The phase sizes of the modified SBS / sulfur-modified asphalt and SBS / sulfur-modified asphalt after long-term aging were 3.38 and 3.58, respectively. This means that the modified SBS / sulfur-modified asphalt had a larger phase size after long-term aging than the original long-term aging SBS-modified asphalt. This aligns with the influence of stabilizers on the performance of SBS-modified asphalt during aging. The addition of stabilizers resulted in smaller changes in the viscoelastic properties of SBS-modified asphalt during aging, indicating that stabilizers have a positive effect on the aging of SBS-modified asphalt. Therefore, this invention solves the problem of the phase size change during the aging process of SBS / sulfur-modified asphalt not conforming to the true law. By separating the influence of sulfurization and aging reactions on phase size, the phase size modified by this invention can be directly used to intuitively judge the degree of SBS polymer degradation in aged SBS / sulfur-modified asphalt.

Claims

1. A method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt, characterized in that... The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt is carried out according to the following steps: I. Preparation of SBS modified asphalt and SBS / sulfur modified asphalt: The two types of asphalt were subjected to short-term aging tests and long-term aging tests, respectively.

2. The morphological characteristics of the two types of asphalt were analyzed, and fluorescence images of the two types of asphalt under three aging states: no aging, short-term aging, and long-term aging were obtained. The Image-pro-plus software was used to perform quantitative analysis on the fluorescence images under the six aging states, calculate the number of SBS polymer phase particles and the particle size of a single particle in each fluorescence image, and draw the SBS polymer particle size distribution map based on the calculated data. III. Combining the SBS polymer particle size distribution map and fluorescence image, we define three quantitative parameters: phase size, phase dispersion, and two phases. Phase size represents the average particle size of the SBS polymer phase; Phase dispersion indicates the uniformity between different particle sizes within an SBS polymer; The two ratios represent the proportion of the bitumen phase to the SBS polymer phase; The formulas for the three quantization parameters are shown below: (1) (2) (3) In the formula: n is the number of SBS polymer particles in the fluorescence image; It represents the area of ​​the SBS polymer phase within the fluorescence image; The area of ​​the bituminous phase within the fluorescence image; i is the sequence number of the SBS polymer particles in the fluorescence image, ranging from 0 to n. The sorting order is based on the area of ​​the SBS polymer particles in the fluorescence image from smallest to largest. IV. Calculation of Sulfation Compensation Factor The specific steps are as follows:

1. Infrared spectral analysis was performed on SBS modified asphalt and SBS / sulfur modified asphalt under three conditions: no aging, short-term aging, and long-term aging. The wavenumber range for the test was 4000 cm⁻¹. -1 ~400cm -1 The resolution is 0.4cm. -1 The corresponding infrared spectra were obtained respectively; 2. For infrared spectra with a wavenumber of 699 cm⁻¹ -1 and 966cm -1 Quantitative analysis was performed on two characteristic groups, and the 699 cm⁻¹ was calculated. -1 and 966cm -1 Characteristic peak area, with wavenumber 699cm² -1 The vibration at this point represents the bending vibration of the CH bond in the benzene ring of polystyrene, with a wavenumber of 966 cm⁻¹. -1 The vibration at this point represents the reverse vibration of the C=C bond in polybutadiene; ① Based on the characteristic group analysis method, calculate the peak areas of the two specific functional groups, which are 699 cm⁻¹ respectively. -1 polystyrene groups and 966cm -1 The polybutadiene group is selected with a wavenumber range of 1800 cm⁻¹. -1 Up to 650cm -1 The peak area is used as a reference peak area to eliminate the influence of film thickness; the relative peak areas are obtained by calculating the areas of the two characteristic peaks and the reference peak area, which are denoted as the styrene index and the butadiene index, respectively, and the calculation formula is shown below; (4) (5) ② Based on Formulas 4 and 5 above, calculate the styrene index and butadiene index of the two types of asphalt in the infrared spectra under the three aging states, and calculate the absolute values ​​of the difference between the styrene index and the butadiene index in the aging reaction. The difference in styrene index during the aging reaction is the styrene index of the unaged product minus the styrene index of the aged product. The difference in butadiene index during the aging reaction is the butadiene index of the unaged butadiene minus the butadiene index of the aged butadiene. ③ Sulfurization compensation factor The sulfidation compensation factors of the two modified asphalts under short-term and long-term aging were calculated using the following formula. (6) In the formula: and These are the differences in the styrene index and the butadiene index, respectively; take the absolute values. It is a sulfurization compensation factor; ④ Take the minimum value of the sulfurization compensation factor in the SBS modified asphalt under the two aging states as the compensation benchmark; standardize the sulfurization compensation factors of the SBS / sulfur modified asphalt under short-term and long-term aging. The standardized sulfurization compensation factor is the corresponding compensation factor divided by the compensation benchmark; then multiply the phase size before compensation by the corresponding standardized sulfurization compensation factor to obtain the phase size after compensation. The phase size after compensation is used to intuitively judge the degree of degradation of SBS polymer in aged SBS / sulfur modified asphalt.

2. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... The preparation method of SBS modified asphalt described in step one is as follows:

1. Shear 90# base asphalt and linear SBS1301 at 180℃ and 4000 rpm for 0.5 hours; the mass of the linear SBS1301 is 5% of the mass of the 90# base asphalt.

2. The sheared sample was then placed in a mechanical mixer and stirred at 500 rpm for 2 hours to obtain SBS modified asphalt.

3. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... The preparation method of SBS / sulfur modified bitumen described in step one is as follows:

1. Shear 90# base asphalt and linear SBS1301 at 180℃ and 4000 rpm for 0.5 hours; the mass of the linear SBS1301 is 5% of the mass of the 90# base asphalt.

2. The sheared sample is first placed in a mechanical stirrer and stirred at 500 rpm for 1 hour. Then, sulfur stabilizer is added and stirring is continued for 1.5 hours, so that the stabilizer reacts with 90# base asphalt and polymer SBS to produce chemical cross-linking and obtain SBS / sulfur modified asphalt. The sulfur stabilizer is 0.15% of the mass of 90# base asphalt.

4. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... The short-term aging described in step one is carried out in a film drying oven under the following conditions: 163°C for 5 hours.

5. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 4, characterized in that... In step one, the short-term aged sample is placed in a pressure aging container for long-term aging. The pressure aging conditions are: 2.1 MPa ± 0.1 Ma pressure, 100℃ for 20 h, to obtain the long-term aged sample.

6. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... The fluorescence image in step two was obtained using a CSM-900E series fluorescence microscope at 400x magnification.

7. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... In step four, the infrared spectrum was analyzed using a Bruker VERTEX 70 series Fourier transform infrared spectrometer.

8. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... The quantitative analysis method described in step 4.2 is based on the Lambert-Beer law, employs the baseline method, and utilizes the analysis function of the Omnic software to calculate 699 cm⁻¹. -1 and 966cm -1 Characteristic peak area.

9. The method for accurately characterizing the degree of SBS polymer degradation during the aging process of SBS / sulfur-modified asphalt according to claim 1, characterized in that... In step 4, the compensated phase size is used to visually determine the degree of degradation of SBS polymer in aged SBS / sulfur modified asphalt. The smaller the compensated phase size, the more severe the degradation and the worse the asphalt performance.